Hippocampal volumes in UK Biobank are associated with APOE only in older adults - Ariya Chaloemtoem; Vera Thornton; Yoonhoo Chang; Andrey P. Anokhin; Michaël E. Belloy; Janine Bijsterbosch; Brian A. Gordon; Sarah M. Hartz; Laura J. Bierut (Alzheimer’s & Dementia: Diagnosis, Assessment & Disease Monitoring)
Abstract INTRODUCTION The hippocampus atrophies with age and is implicated in neurodegenerative disorders including Alzheimer's disease (AD). We examined the interplay between age and apolipoprotein E (APOE) genotype on total hippocampal volume. METHODS Using neuroimaging data from 37,463 UK Biobank participants, we applied linear regression to quantify the association of age and APOE with hippocampal volume and identified the age when volumes of ε2/ε3, ε3/ε4, and ε4/ε4 carriers significantly deviated from ε3/ε3 using generalized additive modeling. RESULTS Total hippocampal volume declined with age, with significant differences by APOE genotype emerging after age 60. ε3/ε4 and ε4/ε4 carriers displayed reduced volumes from ages 69 and 61, respectively, while ε2/ε3 showed delayed decline starting at the age of 76. DISCUSSION The association of APOE and hippocampal volume is age‐dependent, with differences in volumes of ε4/ε4 carriers detected as early as age 61. This work underscores the importance of APOE genotype in determining when to begin screening for AD. Highlights Apolipoprotein E (APOE) genotype shows an age‐dependent association with total hippocampal volume. No association between APOE and total hippocampal volume was detected before age 60. Accelerated decline was observed in ε4/ε4 carriers at age 61 and ε3/ε4 at age 69. Delayed decline was evident in ε2/ε3 carriers starting at age 76.